Geophysical surveys in the vicinity of the Progress station, East Antarctica, performed during the 63rd RAE season (2017/18) - A. Sukhanova A.; S. Popov V.; A. Boronina S.; S. Grigorieva D.; M. Kashkevich P.; А. Суханова А.; С. Попов В.; А. Боронина С.; С. Григорьева Д.; М. Кашкевич П. (Ice and Snow, 2020)
In recent years, when organizing works of the Russian Antarctic Expedition (RAE), considerable attention is given to the safety of logistics operations carried out at Russian stations and field bases. The main factors that threaten polar explorers are extensive systems of cracks and water breakthroughs, confined to the marginal, the most dynamic part of the outlet glaciers, in the area of which the most part of stations are located. One example of the impact of these processes on transport communications in Antarctica is the breakthrough of an intraglacial reservoir in the Dolk glacier near the station Progress (Larsemann Hills, Eastern Antarctica) in the season of the 62nd RAE (2016/17). The outburst resulted in the formation of a huge hole in the glacier body and an extensive system of cracks directed towards its flanks. This took place on the part of the route connecting the Progress Station with the point of organization the sledge-tractor train marches to inner regions of the Antarctic continent. Thus, this destroyed the transport links between these points. That is why during the seasonal works of the 63rd RAE (2017/18) geophysical surveys were carried out around the hole by means of the GPR profiling for the purpose to find the best way and organize a new all-season route. The GPR soundings performed at frequencies of 900 and 150 MHz, made possible to fix numerous cracks and large volumes of melt water accumulations in the near-surface part of the ice layer. The analysis of the obtained time sections and the assessment of the depths of cracks and watered areas did show that the detected objects in the glacier body were not dangerous for advancing of the sledge-caterpillar equipment passing by the hole. These surveys allowed planning the optimal new route, after which it was rolled up and put into operation. The logistical connection between the station and the airfield has been restored. Until the end of the field season, the new all-season route was actively used for transportation. Представлены ...